Dismantling Romantic Utopias: María Beneyto's Poetry Between Tradition and Protest - Candelas S. Gala (Studies in 20th & 21st Century Literature, 1999)
Despite the fact that Vicente Aleixandre considered her one of the best young authors of the generation of social poets of the 1950s, María Beneyto's writings have been disregarded by critics. While sharing the social concerns of the other poets of her generation, Beneyto's poetry also reveals the dilemma of the woman author facing a cultural tradition that espouses pre-established models for her conduct and identity patterned mostly in accordance with tenets of Romanticism. Beneyto resorts to those models as projections of herself as she seeks to articulate her own identity as woman and author. The objective of this essay is to explore Beneyto's reflection on her own identity as woman and poet and, through that process, on the nature of poetic language. By adopting the identity of Eve as the embodiment of instinctual and primitive life that culture has suppressed, or by addressing the role of the mother or angel of the hearth, or the identity of Ophelia, George Sand, or Madame Bovary, Beneyto's poetic speaker hopes to make audible their silenced voices and to contest the rigidity that cultural convention imposes on those roles. Beneyto's poetry destabilizes the essentialism of those models and comes to an understanding of female identity and writing as a constant process of redefinition based on the individual woman's exchanges with the surrounding context.
Keywords: poetry; María Beneyto; woman; woman author; culture; tradition; identity; Romanticism; embodiment; Eve; mother; female identity; context; utopia; Spanish poetry